ANALISIS APLIKASI ANIMASI INTERAKTIF TENTANG PEMBELAJARAN ANATOMI OTAK MENGGUNAKAN PENGUJIAN LOGIC DAN GEOMETRIK MEAN - Akmaludin, Akmaludin (Jurnal Pilar Nusa Mandiri, 2013)
Learning system uses multimedia technology today's is growing rapidly, one of the areas that get a significant impact on the development of technology today's is the field of education. In the process of teaching and learning for students still using the one-way data transfer system by putting the student as an object and as a subject teacher. This makes the students tend to be passive and less showed a level of creativity in the process of knowledge transfer from material provided by the educator to the learner. Learning process in one direction only describes learners listen only, so it is not uncommon cause boredom in the classroom. Learning environment such as this will make it difficult for learners to understand and accept the material provided by the educators. Thus the concept of learning methods with using of interactive multimedia technology to answer these problems, because the multimedia learning with interactive animation to support the learning process by creating a pleasant atmosphere in the learning process, so it is easy for learners to understand and accept the material provided. Interactive animation application design for multimedia-based learning brain anatomy created by Macromedia flash applications, while the analysis used is the white-box testing and analysis of questionnaires using by a geometric mean method. The final results of analysis by the geometric mean method give the results is very good with a making decision score is 88.81.